2002
DOI: 10.2174/0929867023370743
|View full text |Cite
|
Sign up to set email alerts
|

Human Carcinogenesis and Bracken Fern: A Review of the Evidence

Abstract: The complex taxon embraced in the Pteridium genus, popularly known as bracken fern and notorious weeds in many parts of the world, is one of the few vascular plants known to induce cancer naturally in animals. It has been known for long to be acutely toxic to livestock and sublethal chronic oral feeding of bracken fronds leads to cancerous lesions in the urinary bladder, or bovine enzootic haematuria (BEH) and ileum of cattle. Bracken poisoning has been attributed chiefly to ptaquiloside, a norsesqui-terpene w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 64 publications
0
46
0
2
Order By: Relevance
“…It possesses the structure of an illudane and is quite unstable in mildly acidic or basic conditions, decomposing into an illudane-dienone. Additionally, the ptaquiloside aglycone ptaquilosin is also very unstable and decomposes into the same dienone [3,15]. The dienone has been shown to alkylate DNA via a reactive cyclopropyl ring to form a number of different DNA adducts at N3 of adenines, which can lead to point mutations.…”
Section: Bracken Fern As a Cofactor For Carcinogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…It possesses the structure of an illudane and is quite unstable in mildly acidic or basic conditions, decomposing into an illudane-dienone. Additionally, the ptaquiloside aglycone ptaquilosin is also very unstable and decomposes into the same dienone [3,15]. The dienone has been shown to alkylate DNA via a reactive cyclopropyl ring to form a number of different DNA adducts at N3 of adenines, which can lead to point mutations.…”
Section: Bracken Fern As a Cofactor For Carcinogenesismentioning
confidence: 99%
“…Metabolites from ptaquiloside and quercetin along with other chemicals from bracken are also found in the blood, urine and milk of cows naturally exposed to bracken and suffering from bladder cancer [15,80]. Exposure to ptaquiloside indirectly through milk from bracken-grazing cows has a big impact on human health, since it has been correlated with human oesophageal and gastric cancer [3,122,139]. In different parts of the world the human consumption of bracken has been linked to GI cancer [2,3,82].…”
Section: Bracken Fern As a Cofactor For Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have revealed a higher risk of certain types of cancers (i.e., esophageal, gastric) in people who consume bracken fern (or its toxins) directly, as in case of crosiers or rhizomes (Sugimura, 2000;Abnet, 2007), or indirectly through consumption of milk from livestock that have fed on the plant (Alonso-Amelot et al, 1996, 1999Alonso-Amelot, 1997;Shahin et al, 1999;Alonso-Amelot and Avendaño, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The usual procedure before eating (cooking in water, in the presence of different chemicals) serves for removing most, but not all, of the carcinogenic activity. In some countries (Japan, Brazil and Venezuela) a close association was found between the consumption of bracken fern and cancers of the upper alimentary tract (Alonso-Amelot and Avendano, 2002). The frequency of oesophageal and gastric cancer is 5.1-8.1 higher in people with a daily bracken intake than in the people not eating this plant (Marliere et al, 1998).…”
Section: Effects On the Human Organismmentioning
confidence: 99%